Acute kidney injury in cirrhotic patients undergoing contrast-enhanced computed tomography. Issue 38 (September 2016) - Filomia, Roberto; Maimone, Sergio; Caccamo, Gaia; Saitta, Carlo; Visconti, Luca; Alibrandi, Angela; Caloggero, Simona; Bottari, Antonio; Franzè, Maria Stella; Gambino, Carmine Gabriele; Lembo, Tindaro; Oliva, Giovanni; et al.
Abstract : Abstract: Contrast medium administration is one of the leading causes of acute kidney injury (AKI) in different clinical settings. The aim of the study was to investigate occurrence and predisposing factors of AKI in cirrhotic patients undergoing contrast-enhanced computed tomography (CECT). Datasets of 1279 consecutively hospitalized cirrhotic patients were retrospectively analyzed. Two hundred forty-nine of 1279 patients (mean age 64 ± 11 years, 165 male) who had undergone CECT were selected on the basis of the availability of serum creatinine (sCr) values evaluated before and after CECT (CECT group). In analogy, 203/1279 cases (mean age 66 ± 10 years, 132 male) who had not undergone CECT and had been tested twice for sCr in 7 days were also included as controls (Control group). AKI network criteria were employed to assess contrast-induced AKI (CI-AKI) development. Apart from lack of narrowed double sCr measurements, additional exclusion criteria were active bacterial infections, nephrotoxic drugs intake, and estimated glomerular filtration rate <30 mL/min. AKI developed in 22/249 (8.8%) and in 6/203 (3%) of the CECT and the Control groups, respectively ( P = 0.01). The multivariate logistic regression analysis showed that AKI was significantly associated with contrast medium administration (odds ratio [OR]: 3.242, 95% confidence interval [CI]: 1.255–8.375; P = 0.015), female sex (OR: 0.339, 95% CI: 0.139–0.827; P = 0.017), and sCr values (OR: 0.124, 95% CI: 0.016–0.975; P = 0.047). In the CECT group, presence of ascites (OR: 2.796, 95% CI: 1.109–7.052; P = 0.029), female sex (OR: 0.192, 95% CI: 0.073–0.510; P = 0.001), and hyperazotemia (OR: 1.018, 95% CI: 1.001–1.037; P = 0.043) correlated with CI-AKI development at multivariate analysis. CI-AKI is a quite frequent occurrence in cirrhotic patients with female sex, presence of ascites, and hyperazotemia being the predisposing factors.